PetHIS: A New Histopathological Image Dataset for Detecting Breast Cancer in Domestic Canines - Silva, Vinicius Barbosa da; Andrade, Fabio Henrique Evangelista de; Cortes, Omar Andres Carmona (Anais do Workshop de Visão Computacional (WVC); 2023: Anais do XVIII Workshop de Visão ComputacionalDO - 10.5753/wvc.2023.27542, 2023)
Cancer is a severe disease that demands early discovery to increase the chances of survival and the probability of a cure. Its discovery is usually made through biopsy, a slow process subject to fatigue and psychological effects. Building intelligent computational visual tools to accelerate the diagnostic process is crucial in this context. The problem is that tools based on machine learning or deep learning, such as convolutional neural networks, depend on datasets to train the algorithm to create a proper model. Thus, this work proposes a dataset using histopathological images and augmentation of data from examinations of pets by the Laboratory of Veterinary Pathology. Tumor samples were obtained at the Veterinary Hospital School of the State University of Maranhão. Then, the dataset is used in a case study using VGG16 along with double transfer learning to demonstrate the applicability of the dataset. Results show that double transfer learning improves VGG16 efficiency, increasing metrics by around 5% using k-fold with k=5.